Reformulation of the Concept of Iddah in The Compilation of Islamic Law Perspective of Negotiative Hermeneutics - Jannah, Shofiatul; Firdaus, Dwi Hidayatul (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
Iddah is a rule that must be implemented by a woman after divorce from her husband, either due to death or divorce. This is stated in the compilation of Islamic law as one of the regulations in Indonesia. Reformulating of iddah aims to enable Islamic law to address issues in daily life brought about by a variety of changes. For this reason, the author uses a negotiating hermeneutic approach initiated by Khaled M. Abou El Fadl. This research uses a type of literature research (Library research) with qualitative methods. The result of this study finds that iddah obligation is the